General Anesthesia for Direct Laryngoscopy & Bronchoscopy in a Neonate With Stridor - Andrew Pittaway (Association of American Medical Colleges, 2011)
Abstract This problem-based learning resource is designed to promote group discussion and complement relevant clinical exposure/traditional self-directed learning. It is intended primarily for physician-trainee participants in a pediatric anesthesia fellowship program. The resource provides an overview of the wider subject of childhood stridor, as well as current thinking about and various approaches to the clinical conundrum of safely managing the shared pediatric airway under general anesthesia in a neonate with stridor and potentially significant/confounding comorbidity. The material is presented as a narrative case history that poses several key questions crucial to the elucidation of optimal ongoing management. Each of these issues is expanded upon in the subsequent discussion, along with included references and figures depicting the likely pathophysiology and the equipment encountered while dealing with this challenging case. Participants should be given the stem case plus the bibliography ideally a week prior to the intended delivery of the session. The session lends itself well to a small-group round-table discussion of the topic along the lines of the PBL discussions (PBLDs) popularized by many clinical education curricula. One hour is usually sufficient to explore all the major issues. In keeping with PBLD guidelines, no other facilitator resources are necessary. This resource was originally presented as a PBLD at an international anesthesia conference and was created following the author's own experience of dealing with similar clinical complexities and an exhaustive current literature search. The session has been successfully incorporated into an ACGME-approved pediatric anesthesia fellowship didactic education curriculum. To obtain maximum benefit, participants should have sufficient time to research/familiarize themselves with the references-typically 1 week.